Using the SRSD Instructional Approach for Argumentative Writing: A Look across the Content Areas. Issue 3 (19th July 2021) - Peltier, Corey; Garwood, Justin D.; McKenna, John; Peltier, Tiffany; Sendra, Jesse
Abstract: This article will discuss ways to use self‐regulated strategy development for argumentative writing across content areas. The goal of self‐regulated strategy development is for students to generalize the use of the strategy across settings, allowing them to become fluent and proficient writers in all areas. In addition, the generalization of the strategy across settings increases maintenance of skills across time. We will provide steps for educators to use the self‐regulated strategy development instructional approach—more commonly used in reading, writing, and mathematics—across science and social studies content areas with key illustrations using new mnemonics from current practitioners.